Assessing Graduate Competency Fit for the Workplace: A Tracer Study Investigation in Education - Ghea Sekar Palupi; Ardhini Aarih Utami; I Kadek Dwi Nuryana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Effective curriculum programs depend on how well higher education programs prepare people for jobs and how well the job market offers employment opportunities. Unfortunately, many university graduates often work in roles that do not align with what they learned in their studies. This study aims to assess the compatibility between the competencies possessed by graduates of the Information Systems Program at Surabaya State University and the expectations of employers. Method: A tracer study was conducted to investigate the extent to which program graduates are absorbed into the workforce. This research was conducted on alums of the Information Systems Program at Surabaya State University who graduated in 2022. The research method was an online survey with a quantitative descriptive analysis approach. Results: The results revealed that 25.0% of the respondents found the relevance of the Information Systems program to their jobs to be very close, 25.0% considered it close, 37.5% found it quite close, and approximately 12.5% did not find it very close. This indicates that the learning experience provided by the Information Systems program aligns well with job requirements and can be effectively implemented. Novelty: This research focused on aligning the competencies acquired by the Information Systems Program graduates at Surabaya State University. This focused approach on a specific program and year of graduation adds a novel perspective to the broader discourse on the effectiveness of higher education in meeting the demands of the job market.